2005
DOI: 10.1152/ajpheart.00357.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase inhibition and baroreflex sensitivity in humans

Abstract: Animal studies suggest that prostanoids (i.e., such as prostacyclin) may sensitize or impair baroreceptor and/or baroreflex responsiveness depending on the site of administration and/or inhibition. We tested the hypothesis that acute inhibition of cyclooxygenase (COX), the rate-limiting enzyme in prostanoid synthesis, impairs baroreflex regulation of cardiac period (R-R interval) and muscle sympathetic nerve activity (MSNA) in humans and augments pressor reactivity. Baroreflex sensitivity (BRS) was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 41 publications
4
26
0
Order By: Relevance
“…As expected, thromboxane B 2 values were decreased after the ketorolac infusion during baseline as well as after exercise, suggesting that prostaglandin synthesis was attenuated after ketorolac administration (Table 1). These observations are consistent with previous work (5,21,35,54).…”
Section: Discussionsupporting
confidence: 94%
“…As expected, thromboxane B 2 values were decreased after the ketorolac infusion during baseline as well as after exercise, suggesting that prostaglandin synthesis was attenuated after ketorolac administration (Table 1). These observations are consistent with previous work (5,21,35,54).…”
Section: Discussionsupporting
confidence: 94%
“…Notwithstanding these limitations, it should be noted that rats of the present study showed reasonably low HR values (Ͻ400 beats/min), which is a good indicator of an acceptable level of surgical stress, possibly owing to the administration of a long-acting nonsteroidal anti-inflammatory drug before surgery. It is important to note that this class of drugs has been reported not to impair the baroreceptor sensitivity in rats (28) or the sympathetic BRS in humans (21).…”
Section: Discussionmentioning
confidence: 96%
“…Despite a decline in ejection fraction and an increase in end systolic volume in the CM-COX2 KOs, heart rate was suppressed rather than increased via baroreflex activation when compared to controls. Infusion or application of prostaglandins to the carotid sinus have variously been reported to magnify (37) or attenuate (38,39) the baroreflex response, although the relevance of these observations in humans has been questioned (40).…”
Section: Discussionmentioning
confidence: 99%